Active Shooter: What Would Health Care Students Do While Caring for Their Patients? Run? Hide? Or Fight?. (24th April 2020) - McKenzie, Nicole; Wishner, Carolina; Sexton, Martha; Saevig, Danielle; Fink, Brian; Rega, Paul
ABSTRACT: Objective: The aim of this study was to explore the clinical decisions that health care students would make if faced with an active shooter event while providing patient care. Methods: A cross-sectional study design was used to survey 245 students from 6 different professional programs. Participants read 4 case-based scenarios, selected 1 of 4 actions in a multiple-choice format, and responded to an open-ended question. Demographic questions asked whether participants had been a victim of violence and whether they have taken a certified active shooter course. Statistical analysis included descriptive statistics and chi-square testing. Results: For each case, most students chose "patient-centric" versus "provider-centric" actions (range: 66%–94% and 4%–17%, respectively). The gender of the patient made no difference in actions. Those who attended a certified active shooter course tended to act with more "provider-centric" concerns than those who did not take such a course. Conclusion: A significant majority of interprofessional health care students, when presented with specific case-scenarios, declared they would act to protect themselves and their patients during an active shooter event. This "patient-centric" attitude transcends the oversimplified "Run-Hide-Fight" axiom and must be addressed by all health care educational institutions.